Destination attractiveness of a shopping mall: Johor Premium Outlet / Noorsyafiqah Shamsudin - Shamsudin, Noorsyafiqah (2013)
The retail industry in Malaysia is growing by leaps and bounds and has contributed significantly towards the economic development. The contribution of shopping towards overall holiday satisfaction is essential that required concerted effort by the Malaysian authorities to ensure Malaysia is among the top of the list for the tourist shopping destination. Previously, research looked at the importance of price and location of the shopping mall but less attention was paid to the assortment, atmosphere and services especially in Malaysia. This study aims at examining the outlet mall attributes towards visitor’s satisfaction and therefore the correlational study was conducted to satisfy this objective. This study used convenience sampling method and managed to interview 250 respondents. The result shows that atmosphere, assortment and accessibility are the top three attributes that has a strong relationship with visitor’s satisfaction. Outlet mall management must properly manage these attributes and highlights them in the future marketing activities in order to improve satisfaction, and in turn increase profitability.